SKRINING DAN EVALUASI STABILITAS NANODISPERSI TURUNAN IMIDAZOLE SEBAGAI OBAT POTENSIAL ANTI KANKER - Grasianto Grasianto; Amelia Bahetha; Ita Ulfin; Harmami (Chemistry Department, 2025)
Cancer is one of the deadliest complex diseases. Based on data from the International Agency for Research on Cancer (IARC), cancer patients have reached almost 20 million people, with 9.7 million deaths. Nano drugs nano drugs are proposed as a superior alternative as cancer treatment with targeted drug delivery to tumor tissue and controlled release of the intended drug, in this study nano drugs derived from imidazole derivatives that are proven to have good pharmacological activity for cancer treatment will be used, in this study screening will be carried out for potential imidazole derivatives, namely compounds 2,4,5-Triphenylimidazole (IMD 1), 2-(4-nitrophenyl)-4,5-diphenyl-1H-imidazole (IMD 2), 2-(4-Methoxyphenyl)-4,5 diphenyl-1H-imidazole (IMD 3) and 4-(4,5-diphenyl-1H-imidazol-2-yl)-2-methoxyphenol (IMD 4) as nanodrugs and evaluated their stability, and obtained the following results. At the screening of coating materials that are suitable for imidazole derived nanodrugs, namely gelatin, it is analyzed on the stability screening of nanodrug compounds in the biological environment, it is obtained that the IMD 4 nanodrug compound is the most potential nanodrug to be used, because it is still in the EPR size, which is 203.3 nm with the optimal concentration of coating at a concentration of 25 μg/mL. Then in the results of the BCA Assay, it was found that the gelatin that coated the surface of the IMD 4 nanodrug had a maximum coating capacity in the range of 50 μg/mL due to the depletion of the active site on the surface layer of the IMD 4 nanodrug, in the pH stability test of the most potential IMD 4 nanodrug still underwent aggregation, namely with a size of 575.1 nm at pH 5 and with a size of 995 nm at pH 7. The final results of FESEM characterization revealed the surface morphology of IMD 4 nanodrugs in the form of a box, with a size within the EPR range.